Biofilm formation and granule properties in anaerobic digestion at high salinity. (15th September 2017) - Gagliano, M.C.; Ismail, S.B.; Stams, A.J.M.; Plugge, C.M.; Temmink, H.; Van Lier, J.B.
Abstract: For the anaerobic biological treatment of saline wastewater, Anaerobic Digestion (AD) is currently a possibility, even though elevated salt concentrations can be a major obstacle. Anaerobic consortia and especially methanogenic archaea are very sensitive to fluctuations in salinity. When working with Upflow Sludge Blanket Reactor (UASB) technology, in which the microorganisms are aggregated and retained in the system as a granular biofilm, high sodium concentration negatively affects aggregation and consequently process performances. In this research, we analysed the structure of the biofilm and granules formed during the anaerobic treatment of high salinity (at 10 and 20 g/L of sodium) synthetic wastewater at lab scale. The acclimated inoculum was able to accomplish high rates of organics removal at all the salinity levels tested. 16S rRNA gene clonal analysis and Fluorescence In Situ Hybridization (FISH) analyses identified the acetoclastic Methanosaeta harundinacea as the key player involved acetate degradation and microbial attachment/granulation. When additional calcium (1 g/L) was added to overcome the negative effect of sodium on microbial aggregation, during the biofilm formation process microbial attachment and acetate degradation decreased. The same result was observed on granules formation: while calcium had a positive effect on granules strength when added to UASB reactors, Methanosaeta filaments were not present and the degradation of the partially acidified substrate was negatively influenced. This research demonstrated the possibility to get granulation at high salinity, bringing to the forefront the importance of a selection towards Methanosaeta cells growing in filamentous form to obtain strong and healthy granules. Graphical abstract: Highlights: Anaerobic biofilm and granule formation at high salinity (10 and 20 g Na + /L) is possible. UASB reactors process can achieve high removal efficiencies at a salinity as high as 20 g Na + /L. Potassium (0.7 g/L) alleviates the negative effect of 20 g Na + /L on biofilm formation and UASB performance. Calcium (1 g/L) has a negative effect on biofilm formation and reactor performance. The acetoclastic methanogen M. harundinacea is able to grow at a sodium concentration up to 20 g Na + /L.